Developing naturally stress-resistant crops for a sustainable agriculture. (December 2018) - Zhang, Heng; Li, Yuanyuan; Zhu, Jian-Kang
Abstract A major problem facing humanity is that our numbers are growing but the availability of land and fresh water for agriculture is not. This problem is being exacerbated by climate change-induced increases in drought, and other abiotic stresses. Stress-resistant crops are needed to ensure yield stability under stress conditions and to minimize the environmental impacts of crop production. Evolution has created thousands of species of naturally stress-resistant plants (NSRPs), some of which have already been subjected to human domestication and are considered minor crops. Broader cultivation of these minor crops will diversify plant agriculture and the human diet, and will therefore help improve global food security and human health. More research should be directed toward understanding and utilizing NSRPs. Technologies are now available that will enable researchers to rapidly improve the genetics of NSRPs, with the goal of increasing NSRP productivity while retaining NSRP stress resistance and nutritional value. There are multiple strategies to fortify crop nutrition and support global food security and sustainable agriculture. Here the authors propose to increase the diversity of crops by devoting more efforts to studying minor crops that are naturally stress resistant.